A percepção dos honorários na prática clínica por psicoterapeutas - Gross, Camile Moraes (Universidade do Vale do Rio do Sinos, 2008)
The fees theme in the clinical practice is part of the psychotherapeutic relation and reveals itself an important aspect for the psychotherapy course. However, this theme is little investigated in national and international literature. This dissertation focuses on the fees perception in the clinical practice by psychotherapists and comprehends a research report, a theoretical article and an empiric article. The aim of this investigation was the understanding of the fee’ theme in the following theoretical lines: Approach Centered in the Person, Psychotherapy of Analytic Orientation and Behavioral Cognitive Therapy. The research method was exploratory and qualitative. Twelve female and one male clinical psychologists were interviewed. Data were analyzed by content analysis. The aims were to analyze the comprehension of fees’ charge process, the meaning of payment by the client in the clinical practice of psychotherapists and to investigate how the professionals apprehend, in their clinical formation, the lea
Keywords: cobrança de honorários; honorários; prática clínica; preços; psicoterapia; charges; clinical practice; fees; psychotherapy; Ciências Humanas